Manajemen Ekstrakurikuler Seni Batik untuk Mengembangkan Potensi Diri dan Melestarikan Warisan Budaya Takbenda Indonesia - Erna Kartika Sari (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
The research objectives were (1) Knowing the batik art extracurricular management strategy to develop students' self-potential. (2) Knowing the batik art extracurricular management strategy to preserve the Intangible Cultural Heritage of Indonesia for students.The type of research used is descriptive qualitative using data collection techniques through interviews, observation and documentation. The data analysis process is carried out by checking the data list, justifying the feasibility of the data and verifying the data (drawing conclusions). The validity of the data is carried out through the method of member checking, triangulation, extension of participation, persistence of observation and review of negative cases.The results of this study are (1) A well-managed and systematic batik art extracurricular management strategy can develop students' self-potential. (2) A well-managed and systematic batik art extracurricular management strategy can contribute to the preservation of Indonesia's Intangible Cultural Heritage. Keywords : Extracurricular, Batik Arts, Development, Self Potential, Preservation, Intangible Cultural Heritage